Influence of weather factors on population trends of pink bollworm (Pectinophora gossypiella) infesting Bt cotton - V, DESHMUKH K; C S, PATIL; A R, WALUNJ; N K, BHUTE; R S, WAGH; V P, CHIMOTE (The Indian Journal of Agricultural Sciences, 2025)
Pink bollworm [Pectinophora gossypiella (Saunders)] continues to threaten cotton (Gossypium spp.) farming in India, as its larvae are concealed within bolls, making them difficult to control. The present study was carried out during rainy (kharif) season of 2020 and 2021 at Mahatma Phule Krishi Vidyapeeth, Rahuri, Maharashtra to examine the population dynamics of pink bollworm in Bt cotton, focusing on its occurrence and the factors driving its infestation. Cotton variety used for the study was Ajeet-199. The data revealed that in kharif 2020, the number of adult moths captured/week were ranged from 1.00–185.00, with the highest moths catches during the 50th standard meteorological week (SMW) (185 moths/week). In 2021, the trap catches showed a gradual increase, reaching its peak during the 49th SMW (153 moths/week). Rosette flower incidence varied from 2.27–32.84% in 2020 and 2.38–41.67% in 2021. The peaks of rosette flowers were detected during 37th SMW during both the years. During 2020, the extent of green boll damage caused by Pectinophora gossypiella varied from 2.56–63.49%, while in 2021, it was ranged from 4.35–3.49%. The population of pink ballworm (PBW) larvae/20 green bolls ranged from 0.45–38.55 in 2020 and from 1.30–32.50 in 2021, with peak occurrences observed in the 46th and 47th SMW for both the years.